The effect of the guided discovery learning model assisted with google workspace for education towards rhythmic gymnastics learning outcomes - Gede Yudi Septian Permana; Wahjoedi Wahjoedi; I Ketut Sudiana (Universitas Sriwijaya, 2023)
This study aimed at determining; 1) the learning outcomes difference between the students taught by the guided discovery learning model assisted with google workspace for education and the students who were taught by conventional learning, and 2) the interaction between the learning model and learning interest towards students' learning outcomes. True-experimental with a post-test-only control design was used as a research design of this study. The eighth-grade students of junior high school N0 1 Amlapura were involved as the population of this study. Simple random sampling was used to determine this study’s sample from the total population. Test and questionnaire distribution were conducted to collect the data and the instruments used were tests and questionnaires. The collected data were analyzed inferentially statistically by using two ways anova with the assistance of the SPSS 26 program. The results showed that; 1) student learning outcomes using the guided discovery learning model assisted by google workspace for education were higher than those using the conventional model, 2) there was an interaction between the learning model and interest in learning on the learning outcomes of rhythmic motion activities, 3) the learning outcomes of the students who were treated by guided discovery learning model assisted by google workspace for education were higher than the students who were only taught by the conventional model in the high learning interest group, 4) the learning outcomes of the students who were treated by conventional learning were higher than the students taught by applying guided discovery learning model assisted by google workspace for education in a low learning interest group